Nitrogen-doped carbon nanowalls/diamond films as efficient electrocatalysts toward oxygen reduction reaction. (20th October 2021) - Zhang, Chuyan; Huang, Nan; Zhai, Zhaofeng; Liu, Lusheng; Bin Chen,; Lu, Zhigang; Zhou, Meiqi; Song, Haozhe; Shi, Dan; Yang, Bing; Yang, Nianjun; Jiang, Xin
Abstract: Substitution of commercial Pt/C electrocatalysts with efficient carbon-based ones for oxygen reduction reaction (ORR) still remains a huge challenge. For practical ORR applications it is significant to design robust 3D network nanostructures in that they do not require polymer binders. For conventional powder catalysts, they must be combined with substrate, leading to their shedding and degradation. In this work, vertically-aligned N-doped carbon nanowalls/diamond (N-CNWs/D) films are synthesized by means of a microwave plasma chemical vapor deposition technique, where nitrogen doping is conducted during the growth process and a subsequent facile annealing treatment under Ar atmosphere. The obtained Ar treated N-CNWs/D film exhibits an ORR onset potential of 835 mV (versus reversible hydrogen electrode) in 0.1 mol l −1 KOH solution in a four-electron reaction pathway. It also displays excellent tolerance toward methanol crossover and long-term stability (e.g. a current density loss of only 10% even after 16 h measurement). The boosting ORR performance can be attributed to the activated pyridinic N dopant at abundant edge sites and enlarged electrochemical surface areas of N-CNWs/D films. This work not only develops a controllable strategy to fabricate binder-free carbon-based ORR electrocatalysts, but also paves a way to in-depth understand actual active sites in terms of ORR pathway mechanisms.